Financial Ways to Achieve Sustainable Economic Growth and Reduce Inflation - Vladimir Anatol'evich Chernov (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Background: Escalating international tension and economic slowdown across countries have increased the urgency of formulating monetary policy that can support sustainable economic growth. Speculative and fundamental approaches to monetary policy are seen as producing different consequences for economic stability and performance. Objective: This study analyzes the implications of speculative and fundamental approaches to monetary policy on economic development across countries and evaluates the relevance of the benchmark interest rate as a determinant of inflation in Russia. Method: This study uses a dialectical approach with historical and empirical analysis of economic development in Japan, the United States, several European countries, Russia, India, and China. Correlation analysis evaluates the relationship between the Central Bank of Russia’s benchmark interest rate and inflation, accounting for industrial production growth. Results: Using the benchmark interest rate as the main determinant of inflation is not fully consistent, as it disregards the contribution of industrial production growth. The speculative approach is more likely to trigger economic instability, while the fundamental approach better supports economic growth through credit policy that is targeted and oriented toward the productive sector. Conclusion: Monetary policy based on the fundamental approach is more effective in driving economic growth and long-term stability than the speculative approach. This finding supports reformulating monetary policy to better strengthen the productive sector and increase economic competitiveness.